Temephos resistance in Aedes aegypti at Dumai Seaport: implications for vector control - Ardhi, Khairil; Satoto, Tri Baskoro Tunggul; Umniyati, Sitti Rahmah (BKM Public Health and Community Medicine, 2025)
Purpose: This study aimed to assess the resistance status of Aedes aegypti (Ae. aegypti) to temephos at Dumai International Seaport, Indonesia, and to identify the biochemical mechanisms underlying this resistance to support more effective vector control strategies. Methods: An experimental study was conducted using larval bioassays at four concentrations of temephos (0.005–0.625 mg/L) to determine susceptibility levels in field-collected mosquito populations from operational and industrial zones. A laboratory strain was used as a control. Additionally, biochemical assays were performed to measure α-esterase and monooxygenase activity, which are potential indicators of metabolic resistance. Results: Larval bioassays revealed reduced susceptibility to temephos in both operational and industrial populations compared to the laboratory strain. The resistance ratios were 9.75 and 11.75, respectively, indicating moderate to high resistance. Biochemical analysis showed significantly increased α-esterase activity in both field populations (p<0.000), while the seaport population also exhibited elevated monooxygenase activity (p<0.020), suggesting enzyme-mediated resistance mechanisms. Conclusion: The presence of temephos resistance in Ae. aegypti at Dumai Seaport underscores the need to revise existing insecticide use practices. Integrating biochemical surveillance and diverse control measures within the framework of integrated vector management is essential to ensure the sustainability and effectiveness of vector control programs.